(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
This study investigates the colouration and antibacterial functionalisation of silk fabrics using silver nanoparticles (AgNPs). The variation in AgNP morphologies imparted a range of colours to the silk, attributed to differences in the nanoparticles’ localised surface plasmon resonance. The dyed fabrics are characterised for surface morphology, colour strength, and physical and mechanical properties. Transmission electron microscopy (TEM) analysis reveals that the synthesised AgNPs range in size from 2.8 to 79.8 nm. The resulting fabrics exhibit vivid colours corresponding to the morphological variations of AgNPs deposited on their surfaces. Moreover, the AgNP-dyed silk shows strong antibacterial activity against Staphylococcus aureus and Escherichia coli. Cationic pretreatment of silk significantly enhances washing fastness. This study demonstrates that AgNP-based dyeing can be effectively performed at room temperature within a short time, offering a low-energy approach to functionalising silk fabrics.